ANTECEDENTS OF HALAL COSMETICS SUPPLY CHAIN AGILITY PRACTICES: SCALE DEVELOPMENT AND VALIDATION - Nurzalikha Aimi Mohd Subri; Wan Marhaini Wan Omar; An Nur Nabila Ismail3 (Journal of Islamic, Social, Economics and Development, 2024)
Supply chain agility practice plays an important role in the post-Covid-19 era since it enables the assessment and mitigation of supply chain risks particularly in halal industry. Manufacturers are increasingly interested in implementing supply chain agility practices due to the rapid growth of competition in the network. The aim of this study is to develop an instrument and empirically assess the measurement of the antecedents of halal cosmetics supply chain agility practices. The instrument was developed in stages, beginning with identification of antecedents, item generation, questionnaire development, pre-testing, pilot testing, and scale validation. Data were collected from 120 local cosmetics manufacturers across Peninsular Malaysia. Six industrial experts and three academic experts were selected to assess the questionnaire at pre-test phase. The scale was assessed for reliability and validity using Cronbach’s Alpha and Exploratory Factor Analysis (EFA). The scale generated was made up of nine antecedents that were modelled as independent variables covering a total of fifty-two items. As a result, a final instrument of halal cosmetics supply chain agility practices was developed and empirically validated before the main survey took place. Manufacturers and future researchers can use this instrument to further investigate the dimension of supply chain agility practices in other selected industry.